Analysis of Selective User Forwarding in Cell-Free Massive MIMO With Channel Aging - Maria Francis; Farhad Mehran; K. V. S. Hari (IEEE Access, 2023)
Cell-free massive multiple-input-multiple-output (CF-mMIMO) systems provide spectral efficiency (SE) gains with a more uniform quality-of-service in the network area compared to cellular massive MIMO schemes but at the expense of higher capacity requirements on the fronthaul links. To reduce the signaling overhead on fronthaul links, we propose a selective user forwarding method for uplink data transmissions in CF-mMIMO systems, where each access point (AP) forwards the data of only a selected subset of users to the central processing unit (CPU) for joint processing. The simulation results show that the selective user forwarding scheme achieves nearly the same performance as a CF-mMIMO system with selected number of users, $M$ , being equal to less than one-fourth of the total number of users in the network and resulting in a fronthaul signaling savings of about 75%. We then analytically study the performance of the proposed system in the presence of channel aging by deriving expressions for SE. The numerical evaluation of these expressions is shown to be close to the simulation results.